PENGARUH FIRM SIZE DAN FINANCIAL LEVERAGE TERHADAP FINANCIAL PERFORMANCE PADA PT. JAPFA COMFEED INDONESIA - Sumarno Nano; Ade Ponirah; Nurudin Falah (UIN Sunan Gunung Djati Bandung, 2020)
The company's financial performance is the first benchmark to build investor confidence. Describes the state of the company and can be a reference for investment decisions. This article aims to increase the influence of firm size and financial leverage on financial performance of PT.Japfa Comfeed Indonesia firm size shows the size of a company. While financial leverage the proportion of debt usage to finance its investment. This article also uses descriptive methods and quantitative approaches, namely to describe the results of research whose data is presented in numerical form. The data in this article is secondary data taken from financial statements PT. Japfa Comfeed Indonesia, Tbk. and supported by literature and documentation studies, which are processed statistically and quantitatively. The results of this study concluded that partially firm size has an insignificant influence on financial performance. But for financial leverage has a significant influence on financial performance. Simultaneously, firm size and financial leverage have a significant influence on financial performance with a contribution of 66.8% meaning that 33.2% of financial performance is influenced by other factors that are not examined in this study.